Manufacturing of an Innovative Unit for Biochar Production from Agricultural By-Products - Mona A. M. Alghandour; M. M. Morad; K. I. Wasfy; A. E. Azab; M. Zhran (Journal of Applied Science and Engineering, 2024)
The pyrolysis of biomass leftovers for the creation of bio-char was spotlighted in several investigations. However, the bio-char yield affected by pyrolysis temperatures and the carbonization, therefore, we aimed to present a new unit for bio-char production (multi-cylinder movable based one), with efficient uses, operation, maintenance, and produce bio-char with high quality. The newly developed apparatus consists of two primary components: the condenser and the carbonization unit, which together house the stove and the carbonization cylinders. Olive cake was selected as a raw material to verify the manufactured unit for producing bio-char by studying the impact of some functioning features, different temperatures (300, 450, and 600 ◦C) and different carbonization times (3, 4, and 5 h), on the bio-char production unit’s performance. The efficiency of the bio-char production unit was assessed in terms of the bio-char unit outputs, energy needs for the unit’s operation, and the quality of the generated bio-char. Results revealed that the innovative unit successfully produced bio-char from agricultural byproducts in an economically and environmentally friendly manner. The conditions for producing the highestquality bio-char with the best energy efficiency were: pyrolysis temperature of 600 ◦C and carbonization time of 3 h, where the bio-char yield was 37%, the energy requirements for running the unit were 0.39 KWh/kg, and the quality of the produced bio-char was 8.6, 0.42 dS/m (1:10), 32.2 m2/g, and 233% for pH, electric conductivity (Ec), surface area, and water holding capacity, orderly.